THE IMPACT OF THE FLIPPED CLASSROOM METHOD ON LEARNING OUTCOMES - Roozafzai, Zahra Sadat (University of Darussalam Gontor, 2024)
The flipped classroom method, a learner-centered approach, holds potential benefits for EFLinstruction. This study aims to evaluate the effectiveness of the flipped classroom approach inimproving EFL learning outcomes among Iranian undergraduate students. Participants included 120undergraduate EFL learners from an institute in Isfahan. In a mixed-methods approach, studentswere randomly divided into experimental and control groups. The experimental group receivedinstruction through the flipped classroom method, while the control group received traditionalclassroom instruction. Pre- and post-tests were administered to assess the participants' Englishlanguage reading comprehension, grammar, and vocabulary knowledge. In addition, a thematicanalysis was conducted on the students' responses from in-depth interviews to identify and exploreemerging patterns and themes within the data. Paired samples t-test was used to analyze the data.The experimental group demonstrated significantly higher scores on the post-test compared to thecontrol group, indicating that implementing the flipped classroom method in Iranian EFL classroomshas the potential to enhance learning outcomes and motivate students. This study provides evidencefor the effectiveness of the flipped classroom approach in improving EFL learning outcomes amongIranian undergraduate students. Further research could explore the applicability of this approach indiverse cultural contexts and instructional settings. By adopting innovative, learner-centeredmethods like the flipped classroom, educators can transform EFL education and promote studentsuccess.